Introducción a la antropología y arqueología forense - Congram, Derek (2015)
Forensics anthropology and the letter recognized forensic archaeology are fast becoming known, taught and used to assist medic-legal investigations and those of human rights violations (e.g., genocide, crimes against humanity). This article is an introductory description to the fields adding to the very little Spanish literature which currently exists.